Topology Optimization of Spinal Cage Designs for Improved Stress Distribution and Bone Graft Window - Meltem Eryıldız (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Interbody fusion is utilized as a treatment for spinal degenerative diseases. Spinal cages, also known as intervertebral cages or interbody fusion devices, are implants employed in spinal surgery to address these conditions and promote spinal stability. These cages are inserted into the intervertebral space between adjacent vertebrae, replacing the damaged or degenerated disc. Spinal cages aid in the distribution of loads and stress at the fusion site and often incorporate a dedicated area for bone graft material. In this study, a topology optimization approach was employed to develop distinct spinal cages featuring a bone graft window. The mechanical behavior of the spinal cages under loading conditions was simulated and evaluated using finite element analysis. Following optimization, a finite element model analysis estimated the maximum stresses and compared them to the initial model. For topology optimization, reductions of 30%, 50%, and 70% in mass were defined. Both the 50% and 70% mass-reduced designs, featuring an open window, are deemed suitable for bone graft placement and stress distribution.